2013
DOI: 10.14260/jemds/1218
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cervical Cytology in Menopausal Women- In a Maternity and General Hospital, Hyderabad, Andhra Pradesh

Abstract: INTRODUCTION: Cytology, today, is widely used for detection of lesions in the cervix. The realization that invasive cancer of the cervix is preceded by recognizable precancerous histological and cytological changes was one of the most basic contributions that aroused greater interest in the possibility of preventing cancer by early cytological detection. OBJECTIVE: The objective of the study is to investigate the incidence of different epithelial abnormalities of the cervix in menopausal and perimenopausal wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The majority of cases with malignancies in the present study were noted in 60-69 years age group. Mahadik et al 3 and Reddy et al 25 found the highest incidence of malignancies in the age group of 51-60 years as 1.93% and 4.6% respectively. In India the peak age for cervical cancer incidence is 55-59 years.…”
Section: Discussionmentioning
confidence: 94%
“…The majority of cases with malignancies in the present study were noted in 60-69 years age group. Mahadik et al 3 and Reddy et al 25 found the highest incidence of malignancies in the age group of 51-60 years as 1.93% and 4.6% respectively. In India the peak age for cervical cancer incidence is 55-59 years.…”
Section: Discussionmentioning
confidence: 94%
“…A study of Brazil and several studies in India revealed increasing prevalence rate of invasive carcinoma with age (d'Ottaviano-Morelli et al, 2004;Reddy et al, 2013;Ramachandran et al, 2016;Akshatha et al, 2017).…”
Section: Discussionmentioning
confidence: 98%